Improvement of the bladder perfusion curative effect through tight junction protein degradation induced by magnetic temperature-sensitive hydrogels - Sun, Xiaoliang; Song, Xinhong; Guo, Peng; Zhang, Dong; Zuo, Shishuai; Leng, Kang; Liu, Yun; Zhang, Haiyang (Frontiers in Bioengineering and Biotechnology, 2022)
Postoperative intravesical instillation of chemotherapy is a routine procedure for non-muscular invasive bladder cancer (NMIBC). However, traditional bladder perfusion methods have insufficient exposure time, resulting into unsatisfactory therapeutic effects. In the present study, a chitosan (CS)-based in situ forming depot (ISFD) delivery system, including Fe3O4 magnetic nanoparticles (Fe3O4-MNP), CS and β-glycerophosphate (GP) as main components, was synthesized. Pirarubicin (THP), as a chemotherapeutic drug, was loaded into the new system. Results showed that our carrier system (Fe3O4-THP-CS/GP) was converted into gel and attached to the bladder wall, possessing loose network structures with mag-netic targeting and sustained release properties. Moreover, its retention time in bladder was more than 72 hours accompanied by suitable expansion rate and good degradation characteristics. The anti-tumor activities of Fe3O4-THP-CS/GP were more effective both in vitro and in vivo compared with free THP solution. In the study of mechanism, results showed that Fe3O4-THP-CS/GP suppressed the expression of occludin (OCLN) and affected tight junctions (TJ) between urothelial cells to promote THP absorption.